Conserved alarm calls but rapid auditory learning in monkey responses to novel flying objects - Wegdell, Franziska; Hammerschmidt, Kurt; Fischer, Julia (Nature ecology & evolution, 2019)
To evaluate the flexibility in vocal production and comprehension in a non-human primate, we presented a drone to West African green monkeys, Chlorocebus sabaeus . Calls given in response to the drone were clearly distinct from those given to other predators, but highly similar to the aerial alarm calls of the East African vervet monkey, Chlorocebus pygerythrus , suggesting that call structure is conserved. To probe how rapidly the animals attached meaning to the sound of the drone, we played back the drone sound after one to three exposures. Subjects immediately scanned the sky and ran for cover. In contrast to vocal production, comprehension learning was rapid and open-ended. Drone flights observed by West African green monkeys ( Chlorocebus sabaeus ) elicited responses distinct from those for known predators, but which were similar to their East African congenerics, suggesting such responses are conserved.